Flood preparedness intention among Pahang residents: An extension of the theory of planned behaviour - Mohd Rozaimy, Ridzuan; Jamal Rizal, Razali; Noor Amira Syazwani, Abd Rahman; Ju, Soon-Yew (Universiti Teknologi MARA, 2023)
Frequent occurrences of flooding in Malaysia lead to significant loss of lives and property. Pahang, located in the East Coast Region, is particularly vulnerable to severe floods, especially during the monsoon season. Predicting the flood situation in Pahang is challenging as it can unexpectedly affect previously unaffected areas. If the residents of Pahang are conscious of their susceptibility to floods, they are more inclined to make necessary preparations. This study examined the relationship between attitude (ATT), subjective norms (SN), perceived behavioral control (PBC), perceived susceptibility (SUC), and flood preparedness intention (INT) among 200 Pahang residents. A model that was developed was tested using the Structural Equation Modelling (SEM) technique using Partial Least Squares (PLS). A positive relationship was found between the independent variables and dependent variable except for perceived behavioral control. It is hoped that this study can contribute to the body of knowledge regarding flood preparedness in Malaysia, particularly Pahang, Malaysia. This study is also anticipated to assist policymakers in formulating specific policies concerning initiatives aimed at equipping individuals to confront flood situations.